Modern Approaches To Education - Abdullayeva Havokhan (Global Scientific Publishing, 2024)
this article covers the basic principles and approaches of modern pedagogy. It addresses issues such as the activation of the educational process through innovative methodologies, the importance of an individual-oriented approach, and the joint implementation of Education. The importance of the application of information and communication technologies in pedagogical activity, the development of independent thinking of students and the formation of moral values is emphasized.
Keywords: pedagogy; modern education; interactive methods